THE OPTIMIZATION METHOD OF FUZZY AUTOMATIC CLASSIFICATION IN THE PROBLEM OF COMBINING THE ASSESSMENTS OF TRAJECTOR MEASUREMENTS IN THE RADAR SYSTEM - A. V. Khizhniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper describes the application of the optimization method of fuzzy automatic classification in the problem of combining estimates of trajectory measurements in a radar system. By a radiolocation system the author mean an automated hierarchical technical complex that combines, using communication tools, a set of asynchronously functioning radiolocation tools, as well as central and intermediate points that collect, process and issue trajectory radiolocation information. It must be borne in mind that in conditions of tracking tight groups of air targets, with relatively small intervals and distances, it is not always possible to obtain trajectory information of the required quality. The main reason for this is the difficulty in determining the values of the correlation matrices of errors in estimating the parameters of the state vector of air targets. The task becomes more complicated as the number of intermediate processing points increases when it is brought to the final consumer. The main goal of the article is to increase the accuracy of estimates of trajectory measurements in a radiolocation system. The research is done by means of the mathematical tool of fuzz-set theory, namely, by optimizing fuzzy automatic classification. The article demonstrates that using fuzzy automatic classification under a priori parametrical uncertainty in the law of trajectory measurement errors, when determining weight coefficients, can improve the accuracy of estimates in these conditions up to 30 % compared with methods based on the application of the probabilistic approach. The results obtained allow us to justify the prospects of using optimization methods of fuzzy automatic classification in the tasks of processing trajectory information. In addition, the advantage of the proposed method is its low computational complexity and ease of implementation, which is especially important while maintaining a large number of airborne objects.